575 Team science training needs and preferences for clinical research professionals: A focus group analysis - Jessica Fritter; Bernadette Capili; Jackie Knapke; Shirley Helm; Elizabeth Kopras; Jill McCabe; Meredith Fitz-Gerald; Mendell; Carolynn T. Jones (Journal of Clinical and Translational Science)
Objectives/Goals: To present findings from a focus group study that evaluate clinical research professionals’ (CRPs) team science learning preferences. The study aims to better understand CRPs’ experiential perceptions of team science skills, training gaps, team cohesion, conflict, and contributions for their preferred team science training. Methods/Study Population: This study targeted CRPs across various roles in Academic Health Centers via focus groups. The focus groups will assess current skills, identify training gaps, and share experiences on team cohesion, team conflict, team contribution, and their thoughts and perceptions about clinical research professional team science training. The focus groups will be held via Zoom in the Autumn of 2024 with volunteer participants from an initial survey that was conducted earlier in 2024. We will report on combined data from multiple 90-minute focus groups, with approximately 6 participants per session. Results/Anticipated Results: The focus group facilitator’s guide includes questions informed by the CRP team science learning needs assessment results and other questions on team issues that would benefit from focused training. Focus group methods and demographic characteristics of the participants by role and experience level will also be presented. Qualitative analyses of recorded focus-group discussions will present key themes by demographic groups, and as a whole, these data will contribute to the development of CRP team science educational programs and toolkits. Discussion/Significance of Impact: CRPs are vital members of clinical translational science teams. Overlooking CRP team science training can negatively affect the efficiency and effectiveness of the clinical translational science enterprise. CRP team science skills will foster a more collaborative and productive research environment.